Upper-limb power test in rock-climbing - Laffaye, G.; Collin, J.-M.; Levernier, G.; Padulo, J. (International Journal of Sports Medicine, 2014)
The goal of the present study was to validate a new ecological power-test on athletes of diff erent levels and to assess rock climbers` profi les (boulderers vs. route climbers). 34 athletes divided into novice, skilled and elite groups performed the arm-jump board test (AJ). Power, time, velocity, and efficiency index were recorded. Validity was assessed by comparing the distance with the value extracted from the accelerometer (500 Hz) and the reliability of intra- and inter-session scores. Moreover, a principal component analysis (PCA) was used to assess the climbers` profi les. The AJ test was quite valid, showing a low systematic bias of - 0.88 cm ( - 1.25 %) and low limits of agreement ( < 6 %), and reliable ( Intraclass correlation coeffi cient = 0.98 and CV < 5 %), and was able to distinguish between the 3 samples (p < 0.0001). There was a good correlation between relative upper-limb power (r = 0.70; p < 0.01) and the AJ score. Moreover, the PCA revealed an explosive profile for boulderers and either a weak and quick or slow profi le for route climbers, revealing a biomechanical signature of the sub-discipline. The AJ test provides excellent absolute and relative reliabilities for climbing, and can effectively distinguish between climbing athletes of different competitive levels. Thus, the AJ may be suitable for field assessment of upper limb strength in climbing practitioners.